Silica Aerogel Hybridized with Melamine-Terephthalaldehyde Polymer for In-Tube Solid-Phase Microextraction of Polycyclic Aromatic Hydrocarbons from Environment Water - Qiong Jiang; Shuwu Zhang; Juanjuan Feng; Min Sun (Nanomaterials, 2022)
To improve the extraction performance of the silica aerogel, a melamine-terephthalaldehyde polymer was used to hybridize silica aerogel, and the hybridized aerogel was coated on the surface of stainless steel wire to prepare a fiber-filled extraction tube through placing four wires into a polyetheretherketone tube. The tube was combined with high-performance liquid chromatography, then the online extraction and detection were established. Several polycyclic aromatic hydrocarbons (PAHs) were selected as the target analytes. Under the optimum extraction and desorption conditions, the limit of detection was as low as 3.0 ng L−1, and the linear range was 0.01–20.0 μg L−1. The enrichment factors of PAHs were in the range of 1724–2393. Three environmental water samples of mineral water, tap water and river water were analyzed by this method, and the recoveries that spiked at 1.0–10.0 μg L−1 were between 80.5–126%. It showed many advantages compared with other methods, such as better sensitivity, faster detection and online analysis.